58 How to turn a sow's ear into a silk purse: rapid culture change to improve performance and headlines. (12th November 2018) - Hosking, Emma-Jane; Robinson, Gareth
Abstract : Our hospital's unscheduled care performance last winter was poor with long delays for assessment and admission, crowding in our emergency department (ED) and an apparent inability to improve. PricewaterhouseCooper (PWC) were commissioned to work with us to change this. We have moved from a system of 'bed management' meetings (sometimes several times a day) led by nurses to a system leadership model led by senior members of the hospital management team (HMT). Key to this is the daily safety huddle which is a multi-professional meeting inclusive of clinical and non-clinical staff. In addition we introudced two-hourly safety huddles in the ED led by the nurse in charge. This has improved our ambulance handover time, reduced surgical cancellations, reduced critical care cancellations for elective and urgent surgery and reduced delayed transfers of care from critical care. Cultural change included redefining the role of directors, improving cooperation between departments, and recognition of the interdependency of services and clinical areas. The leaders were required to be visible, coach, demonstrate adaptability, use humour and to listen with fascination to coleagues' reservations. Qualitative improvements include better integration with coleagues in community care, more confidence in the process (eg willingness to go ahead with surgery even when a bed isn't immediately available), better 'grip' in ED and the leadership development of operational managers and clinicians.